THE RELATIONSHIP BETWEEN INFLATION AND ECONOMIC DEVELOPMENT IN CONTEMPORARY BRAZIL: ADVANCES AND SETBACKS - Pereira da Silva Leão, Airton; Samelyne Lima da Silva, Layza; Melo Costa Simões, Valéria; Gustavo Portela dos Santos, Mikael (Revista Gênero e Interdisciplinaridade, 2026)
Understanding the dynamics between inflation, interest rates, and economic growth is one of the central pillars of contemporary macroeconomic analysis, especially in a context marked by cyclical instabilities, external shocks, and constant adjustments in economic policy. Among the main indicators, inflation, interest rates, and Gross Domestic Product (GDP) stand out, whose interrelationship has been widely debated in the economic literature, especially regarding their effects on growth and macroeconomic stability. In this sense, fundamental questions emerge: to what extent do these indicators correlate over time? Does inflation control policy, through interest rates, significantly influence GDP performance? And what empirical evidence can be observed in the Brazilian context? Given these questions, this article aims to analyze historical series of these indicators in Brazil, seeking to identify correlation patterns and understand the possible influence of inflation on national economic development, contributing to the academic debate and the formulation of more efficient public policies.